The Care of Childhood Cancer Survivors in India: Challenges and Solutions - Prasad, Maya; Goswami, Savita; Kurkure, Purna A. (Indian Journal of Medical and Paediatric Oncology, 2023)
Purpose We describe the challenges faced and lessons learnt over three decades of a childhood cancer survivorship program in India.Methods We provide a descriptive analysis of the challenges and barriers faced in running this program, our strategies in management, and detail the stages of development of holistic support system.Results The profile of late effects in our cohort of survivors is notable for the high prevalence of psychosocial issues and metabolic syndrome. Major difficulties faced were transitioning of patients to survivorship care and attrition to follow-up, which were overcome to an extent by ensuring constant communication/rapport-building, updated databases, and peer support groups. Collaborations with nonprofit organizations and other donors have enabled financial, psychosocial, educational, and vocational rehabilitation.Conclusions It is feasible to establish and sustain a survivorship program in a large-volume center in low- and medium-income country. Understanding the unique spectrum of late effects and establishing a holistic support system go a long way in ensuring the long-term physical and mental health and psychosocial concerns of childhood cancer survivors. Decentralization, development of a strong national networks, capacity building, and incorporation of sustainable technology should be priorities in survivorship care.
Keywords: childhood cancer survivors; low- and middle-income countries; survivorship care